Has learning gone to waste?—Health-promoting behaviors of seniors - Dąbek, Józefa; Szynal, Magdalena; Sierka, Oskar; Łebek, Ewelina; Kulik, Halina (Frontiers in Public Health, 2024)
Regardless of the fact that Universities of Third Age (UTA's) are becoming more and more popular among seniors there are not many available studies examining the impact of conducted educational activities on seniors' adherence to health-promoting activities. The aim of the study was to compare health behaviors (e.g.: physical activity, eating habits, alcohol consumption, tobacco smoking, preventive tests performance) between seniors attending and not attending UTA’s classes. The study involved 631 (100%) seniors aged 60 to 92 years (x ̅=70.28±6.09 years). The majority of the study group were women (475; 75.28%). To conduct the study, a proprietary questionnaire was used, consisting of questions regarding the discussed topic and basic questions including: age, gender, place of residence and education. Polish versions of standardized questionnaire – “My eating behaviors” examine eating behaviors of the respondents. The Chi2 test was used for qualitative data, and for quantitative data - the Mann-Whitney U test (No normal distribution: T S-W<0.001). Linear and logistic regression models were use to check whether the associations would remain after adjustments for potential cofounders. The level of statistical significance was set at α<0.05.Number of seniors participating in UTA’s activities was higher in terms of engaging in: actively spending free time (261; 73.73% vs. 93; 26.27%; p<0.001), regular physical activity (270; 76.27% vs. 133; 48.01%; p<0.001), self-assessment of physical activity (259; 73.16% vs. 95; 26.84%; p=0.004), duration of physical activity (<0.001), past tobacco smoking (133; 37.57 vs. 76; 27.44%; p=0.007) and alcohol consumption depending on the habit frequency (p<0.001). Number of seniors not participating in UTA’s classes was lower in terms of: regular annual dental controls (161; 58.12%; vs. 265; 74.86%; p<0.001), regular self-examination of breasts/testicles (148; 53.43% vs. 218; 61.58%; p=0.04) and regular laboratory tests (232; 83.75% vs. 318; 89.83%; p=0.02). Health-promoting behaviors of seniors attending classes at the UTA’s were more correct in terms of physical activity, adequate attendance with preventive test and worst in terms of alcohol consumption. Overall picture allows to conclude that participation in UTA's classes seems to have a positive impact on the examined health-promoting behaviors of the surveyed seniors.